Strategi Komunikasi Humas Partai Politik Gerindra Dalam Menjaring Pemilih Pemula Melalui Media Sosial - Yanuar Ilham; Andi Chandra Hermawan (LPPM UNIBI, 2022)
The demographic bonus phenomenon experienced by Indonesia makes novice voters a big market that must be obtained by political parties, this makes political parties carry out new communication strategies in capturing novice voters, the characteristics of novice voters are those who are always connected to social media. The Gerindra Party's Public Relations Communication Strategy in Capturing Beginner Voters on Valentine's Day Momentum in 2022 through the Twitter @gerindra Social Media Account. This study aims to find out how the steps taken by the Gerindra Party in capturing novice voters through social media twitter on the momentum of Valentine's Day in 2022, the obstacles experienced, the views of Twitter followers @gerindra, and how to use the momentum of Valentine's Day in 2022 the Gerindra Party. to capture novice voters. This research uses a qualitative case study approach using the concept of communication strategy steps proposed by Onong Ucjana Effendy in 2011. The object of this research is Twitter @gerindra. The data obtained in this study were obtained from observations, interviews, library studies, and documentation. The results of this study explain the steps of the Gerindra Party's communication strategy in capturing novice voters, the obstacles experienced are that the features available on Twitter addition to accusations of gratification to the Gerindra Party, Positive views from Twitter followers @gerindra they are happy with what carried out by the twitter @gerindra, The Gerindra Party's explanation in taking advantage of the momentum of Valentine's Day in 2022 is to attract novice voters by knowing the problems experienced by novice voters and the Gerindra Party trying to get in to be a solution to the love problems of novice voters.